Sistem Pakar Identifikasi Penyakit Hipertensi Pada Ibu Hamil Menggunakan Metode Certainty Factor - Sabda Novita; Hari Aspriyono; Lena Elfianty (JUKI : Jurnal Komputer dan Informatika, 2023)
This study aims to create an expert system application to diagnose hypertension in pregnant women using the Certainty Factor method. Hypertension is high blood pressure which causes various health problems. The problem that often occurs is the lack of knowledge and limited sources of information which causes low public awareness of efforts to prevent and even treat hypertension. The MySQL database can accommodate information and data on patients who consult with expert systems that can make it easy for patients to consult about hypertension. From the results of the system program for users, it was obtained that the average response of respondents reached 63% who answered strongly agreed, 26% answered that they agreed, 7% answered that they did not agree and only 4% of respondents answered that they did not agree. So from the results of data processing it can be interpreted that this system is feasible to use. Because more than 50% of the total respondents agree that this system is feasible to use.